2018
DOI: 10.1126/scitranslmed.aao2301
|View full text |Cite
|
Sign up to set email alerts
|

Afatinib restrains K-RAS–driven lung tumorigenesis

Abstract: On the basis of clinical trials using first-generation epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), it became a doctrine that V-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog () mutations drive resistance to EGFR inhibition in non-small cell lung cancer (NSCLC). Conversely, we provide evidence that EGFR signaling is engaged in K-RAS-driven lung tumorigenesis in humans and in mice. Specifically, genetic mouse models revealed that deletion of quenches mutant K-RAS activity and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
94
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 52 publications
18
94
0
Order By: Relevance
“…Intriguingly, global gene expression analysis revealed that K‐ras G12D expression resulted in activation of the JAK–STAT pathway (Figs. S3 a and S3 b ) . Encouraged by these data, we treated K and KP mice 1 week after tumor induction with ruxolitinib or vehicle control for a period of 10 weeks, euthanized them and analyzed their lungs.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Intriguingly, global gene expression analysis revealed that K‐ras G12D expression resulted in activation of the JAK–STAT pathway (Figs. S3 a and S3 b ) . Encouraged by these data, we treated K and KP mice 1 week after tumor induction with ruxolitinib or vehicle control for a period of 10 weeks, euthanized them and analyzed their lungs.…”
Section: Resultsmentioning
confidence: 99%
“…For subcutaneous xenograft experiments using the K‐RAS ‐mutated human lung AC cell lines A549 and A427, 1 × 10 6 cells were mixed 1:2 with Matrigel (Corning, Corning, NY) and injected into the right and left flank of immunodeficient NOD scid gamma mice older than 6 weeks of age. Tumor volume was measured using a caliper and tumor volume was calculated using the formula [(length × width 2 ) × 0.52] as previously established in our laboratory …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations